Bibliometric Analysis of Teacher Leadership Using VOSviewer - Hidayat, Rais; Patras, Yuyun Elizabeth; Sampaleng, Donna; Gunawan, Yusuf (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This article aims to identify publications on the teacher leadership theme comprehensively. The publication data is from articles, reviews, and English and comes from the Scopus database from 1993 to 2022. The keyword used in the data search is